Effect of Coffee Cascara Dietary Fiber on the Physicochemical, Nutritional and Sensory Properties of a Gluten-Free Bread Formulation - Rios, Maria Belen (Molecules, 2020)
This study aimed to assess the physicochemical, nutritional and sensory properties of gluten-free breads containing isolated coffee cascara dietary fiber (ICCDF) as a food ingredient. ICCDF was obtained by aqueous extraction. The oil and water holding capacity and the nutritional profile of the novel ingredient were determined. Its safety was certificated by analysis of ochratoxin A, caffeine and gluten. Gluten-free bread formulations were prepared enriching a commercial bakery premix in rice protein (8%) and ICCDF (3% and 4.5%). Nutritional profile of the novel gluten-free breads (dietary fiber, protein, amino acids, lipids, fatty acid profile and resistant starch), as well as bread volume, crumb density, moisture, firmness, elasticity and color intensity were determined. A sensory quantitative descriptive analysis of the breads was conducted using eight trained panelists. New breads showed significantly higher (p < 0.05) content of dietary fiber and protein than the control bread. The addition of ICCDF allowed increasing dough yield, a less crumb firmness and a higher crumb elasticity. The nutrition claims “source of protein and high in dietary fiber” were assigned to the new formulations. In conclusion, a certificated gluten-free bread with improved nutritional and physicochemical properties and good sensorial profile was obtained.